Study of orbitally excited $B$ mesons and evidence for a new $Bπ$ resonance - Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; Ashmanskas, W; et al. (American Physical Society, 2013)
Using the full CDF Run II data sample, we report evidence for a new resonance, which we refer to as $B(5970)$, found simultaneously in the $B^0π^+$ and $B^+π^-$ mass distributions with a significance of 4.4 standard deviations. We further report the first study of resonances consistent with orbitally excited $B^{+}$ mesons and an updated measurement of the properties of orbitally excited $B^0$ and $B_s^0$ mesons. We measure the masses and widths of all states, as well as the relative production rates of $B_1$, $B_2^*$, and $B(5970)$ states and the branching fraction of the $B_{s2}^{*0}$ state to either $B^{*+} K^-$ and $B^{+} K^-$. Furthermore, we measure the production rates of the orbitally excited $B^{0,+}$ states relative to the $B^{0,+}$ ground state. The masses of the new $B(5970)$ resonances are $5978±5(stat)±12(syst) MeV/c^{2}$ for the neutral state and $5961±5(stat)±12(syst) MeV/c^{2}$ for the charged state, assuming that the resonance decays into $Bπ$ final states. The properties of the orbitally excited and the new $B(5970)^{0,+}$ states are compatible with isospin symmetry.